PENGARUH KUALITAS YANG DIRASAKAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPERCAYAAN SEBAGAI PEMEDIASI PADA PELANGGAN FATMA SALON DI KOTA BANDA ACEH - Fitria Dewi Ananda, Saed Armia (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract: This study aims to determine the effect of perceived quality on customer loyalty with customer trust as a mediator. The empirical study was conducted on Fatma Salon in Kota Banda Aceh using questionnaire as research instrument, which the sample in this research is 160 people. Nonprobability Sampling is used as sampling technique with Purposive Sampling method. HLM (Hierarchical Linear Modeling) method is used as data analysis method using IBM SPSS 22 software. The result of this research indicates that perceived quality have positive and significant effect to customer loyalty, perceived quality have positive and significant influence to customer trust, customer trust have positive effect and significant to customer loyalty and in addition to the result that customer trust mediates the positively and significantly influenced quality effect on customer loyalty. So the mediation relationship is called partial mediation.